New nematogenic conical-shaped supramolecular H-bonded complexes for solar energy investigations - Sobhi M. Gomha (Nature Portfolio, 2021)
Abstract New conical-shaped geometrical supramolecular H-bonded liquid crystal complexes were formed through 1:2 intermolecular interactions of H-bonding between flexible core (adipic acid, A) and lateral chloro-substituted azopyridines (Bn). The chains of the terminally alkoxy substituted base (n) were changed between 8 and 16 carbons. Mesomorphic and optical examinations of the prepared complexes were measured via differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). Fourier-transform infrared spectroscopy (FT-IR) was used to confirm the Fermi bands of the H- bonding interactions. Induced nematogenic mesophases that cover the whole lengths of alkoxy-chains were detected. The non-linear geometries of the designed supramolecular complexes were also confirmed via Density functional theory (DFT) calculations. It was found that the length of terminal alkoxy chain of the base moiety highly affects the geometrical structure of the investigated complexes. Moreover, it increases the thermodynamic energy and influences the geometrical parameters. The electrical properties of each of the acid component (A), the base (B16) and their 1:2 complex (A/2B16) were evaluated using the Keithley measurement-source unit. The optical properties studies showed that the influences in the optical absorption and the reduction of the energy gap of the complex compared to its individual components made the resulted supramolecular H-bonded complex soft material suitable for solar energy investigations.